CTNI-24. A PHASE 1/2 STUDY OF AVAPRITINIB IN PEDIATRIC PATIENTS WITH SOLID TUMORS DEPENDENT ON KIT OR PDGFRA SIGNALING. (12th November 2021) - Chi, Susan; Hsieh, Antony; Foley, Megan; Shi, Hongliang; Swamy, Preethi; Rodstrom, Jill; Rudoltz, Marc
Abstract: Prognosis for pediatric patients with advanced relapsed/refractory (R/R) solid (including central nervous system [CNS]) tumors is poor; response rates are only 15% with targeted therapies. Germ cell tumors and high-grade glioma (HGG) are the most common with KIT alterations; sarcoma and HGG are the most common tumors with platelet-derived growth factor receptor alpha ( PDGFRA ) alterations. H3K27M gliomas are dependent on PDGFRA signaling and patients have an overall survival of 1 year. No KIT/PDGFRA targeted therapies are currently approved for pediatric patients with R/R solid or CNS tumors, or H3K27M gliomas. The selective KIT and PDGFRA inhibitor, avapritinib, demonstrated potent activity against KIT activation-loop (exon 17), juxtamembrane (exon 11), and extracellular-domain (exon 9) mutants (IC50 < 2 nM), and PDGFRA activation-loop (D842V) mutants (IC50 = 0.24 nM); cellular IC50 of PDGFRA wild-type was 95 nM. CNS penetration in preclinical models (brain-to-plasma ratios at steady-state ranging from 0.74–1.00) demonstrated potential for CNS antitumor activity. Avapritinib is approved for the treatment of adults with unresectable/metastatic gastrointestinal stromal tumors (GIST) harboring PDGFRA exon 18 mutations (including D842V) in the USA, and in the EU for adults with unresectable/metastatic GIST harboring a PDGFRA D842V mutation. Objectives of this 2-part phase 1/2, multicenter, open-label study are to assess avapritinib safety, preliminary efficacy, and pharmacokinetics in pediatric patients aged 2 to < 18 years with solid R/R tumors dependent on KIT or PDGFRA signaling, including H3K27M gliomas and no alternative treatment options. Part 1 will enroll ≥ 6 patients; primary endpoint is confirmed age and body surface area physiologically-based pharmacokinetic modeling dose to provide equivalent exposure to the 300 mg adult avapritinib dose. Part 2 will enroll ≥ 25 patients at the recommended avapritinib dose from Part 1; primary endpoint is objective response rate. Avapritinib once-daily will be administered in continuous 28-day cycles.